BENCHMARKING: Políticas Públicas de Incentivo a Geração de Energia Fotovoltaica - dos Santos, Bruno Campos; Costa Filho, Antônio da Fonseca; Nichioka, Júlio (Episteme Transversalis, 2019)
O objetivo geral deste artigo é descrever o estado da arte, referente aos mecanismos de incentivo à geração de energia solar, com o intuito de proteger o meio ambiente. O objetivo específico, foco desse artigo, foi apurar as boas práticas nas políticas de incentivo à geração de energia através das fontes renováveis, em especial, a energia solar, e a forma de estruturação para a implementação de políticas públicas de promoção a fontes renováveis, o caminho percorrido para responder aos questionamentos deste trabalho, demonstrou, haver grande similaridade entre as políticas adotas pelos 3 países líderes na geração fotovoltaica: China, Japão e Alemanha. Portanto, constatou-se que as melhores políticas na promoção de energia solar, são Feed-in Tariff e Leilões com contas para energias renováveis, em decorrência da utilização dessas políticas pelos países analisados.  Abstract The general objective of this article is to describe what is the state of the art when it comes to mechanisms to encourage the generation of solar energy, with the aim of protecting the environment. The specific objective, the focus of this article, will be to determine which good practices in policies to encourage the generation of energy with the use of renewable sources, in particular the generation of solar energy, and the form of structuring for the implementation of public policies of promotion to renewable sources, which the world leader in photovoltaic power generation has employed. In this study, the three largest producers of solar energy, China, Japan and Germany, were analyzed. In this study, the three major producers of solar energy were analyzed. Therefore, it has been proven that the most successful policies in promoting solar energy are Feed-in Tariff and Auctions with accounts for renewable energy. The fact that this argument has proven, the full use of these policies by the leading countries in the world solar generation.